43+T Grenoble hybrid magnet: Commissioning tests of the current leads and cryogenic satellite producing the pressurized superfluid He at 1.8 K. Issue 1 (1st May 2022) - Pugnat, P; Barbier, R; Berriaud, C; Boujet, T; Graffin, P; Grandclément, C; Hervieu, B; Jousset, J; Juster, F P; Molinié, F; Pelloux, M; Pfister, R; et al.
Abstract: The Grenoble Hybrid magnet is a modular platform using resistive and superconducting technologies to produce various continuous high magnetic field and flux configurations for the scientific community. They range from 43 T in 34 mm diameter with 24 MW electrical power to 9 T in 800 mm diameter when the superconducting coil is used alone. Thanks to the ongoing upgrade of the electrical power installation of LNCMI-Grenoble up to 30 MW and possibly to 36 MW, the possibility to increase the total field up to 45-46 T in the near future is foresee and deeply studied. The key design parameters will be briefly recalled including the specifically developed Nb-Ti/Cu conductor, the large bore outsert superconducting coil, the magnet cryostat with its structure including the eddy-current shield, the cryogenic line for the interconnection with the cryogenic satellite and the fully dedicated 150 l/h He liquefaction plant. All components of the hybrid magnet platform have been built, tested and delivered to LNCMI-Grenoble, where integration and assembly are ongoing. The status of the project will be given with focus to the recent commissioning tests of the cryogenic satellite producing the pressurized superfluid He at 1.8 K as well as to the successful powering tests of the specially developed current leads at ultimate current and under fully degraded cooling conditions simulating the worst-case accidental scenario.